Analysis of the Performance Evaluation of the Population and Civil Registration Service of Surabaya City using the Performance, Information, Economic, Control, Efficiency, Services (PIECES) Method - Muhammad Yazid Basthomi Maliki; Puteri Noraisya Primandari (Yayasan Banu Haji Samsudin, 2025)
The research was conducted to meet the needs of users, namely the people of Surabaya City, for that it is necessary to have an analysis and evaluation of the measurement of the level of user satisfaction with the population administration information system at the Surabaya City Population and Civil Registration Service, namely the Klampid New Generation website. The data collection methods used were interviews, observations and questionnaires. In this study, the system evaluation method used the PIECES method consisting of 6 aspects of Performance (performance) Information (information), Economy (economy), Control (control), Efficiency (efficiency), and Service (service). Analyzing the questionnaire data, descriptive statistics were carried out to determine the characteristics of the data, validity and reliability tests to determine the quality of valid/accurate and reliable questionnaire data. normality test, correlation test and multiple linear regression test. Then evaluate the system by calculating the average questionnaire results to determine the level of satisfaction. The results of the study showed that the average level of satisfaction from the 6 aspects of the PIECES method was Performance 3.81 with the Satisfied category, Information 4.16 with the Very Satisfied category, Economic 3.95 with the Satisfied category, Control 4.06 with the Satisfied category, Efficiency 3.88 with the Satisfied category, and Services 3.87 with the Satisfied category. Based on the calculation results for each PIECES Framework variable, the total average value obtained was 3.95 with the description Satisfied, so it can be concluded that the Klampid New Generation website provides satisfactory results for its users. 5 categories of Satisfied and 1 Very Satisfied so that the Klampid New Generation population administration information system is quite effective and efficient for users, especially the people of Surabaya City and is a material for further development. The results of linear regression show that all 6 aspects of the PIECES method have a significant influence on user satisfaction.